2022
DOI: 10.3390/buildings12111805
|View full text |Cite
|
Sign up to set email alerts
|

A Phase-Based Roadmap for Proliferating BIM within the Construction Sector Using DEMATEL Technique: Perspectives from Egyptian Practitioners

Abstract: Building Information Modelling (BIM) has not been sufficiently proliferated in the developing construction communities. This is owing to the lack of incorporating the key success factors (KSFs) of BIM implementation in a phase-based roadmap to support implementing BIM in practice on a step-by-step approach. With this in mind, this work aims at (1) defining the KSFs for implementing BIM within the developing economies’ socio-economic environment, (2) investigating the interrelationships among the KSFs, and (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In the current research paper, authors have identified the CSFs of implementing CE in Indian SMEs and have prioritized them using the Fuzzy Decision-making trial and evaluation laboratory (DEMATEL) techniques. This technique develops the interrelationship between the CSFs and helps in differentiating the influential CSFs [77]. This technique has been found to be useful in finding interrelationships between factors in any system [37].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current research paper, authors have identified the CSFs of implementing CE in Indian SMEs and have prioritized them using the Fuzzy Decision-making trial and evaluation laboratory (DEMATEL) techniques. This technique develops the interrelationship between the CSFs and helps in differentiating the influential CSFs [77]. This technique has been found to be useful in finding interrelationships between factors in any system [37].…”
Section: Methodsmentioning
confidence: 99%
“…This technique has been favored in comparison with other multi-criteria decision making (MCDM) techniques due to its characteristics of being a structural modeling technique with the capability of differentiating factors in two groups of cause and effect, by exploring their relationship and severity. This technique also gives experts a wide range of replies (0, 1, 2, 3, and 4) (Table 3) [15,38,77]. SMEs can form strategies based on quantitative and visual kinship among CSFs through an impact relation diagram [77].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The virtual components may be queried by members of the project to retrieve previously saved information or to upload new information [68]. For instance, designers are able to include information on design assessments into the virtual systems, which can then be transferred to tags on the physical components and viewed on the site, and vice versa [36]. Virtual models also serve as a platform for remotely controlling physical systems, such as lighting electrical components during the operation and maintenance phase.…”
Section: Creation Of Workable Virtual Modesmentioning
confidence: 99%
“…Sometimes, however, BIM suffers from overly ambitious usage without a discreet examination and assessment of its effectiveness, which means that BIM can fail to realize its expected value and causes undesirable disruption to the project workflow [3,4]. BIM implementation in the AECO industry staggers within a dilemma whether to follow the well-established convention or adapt to the new disruptive approach [5][6][7]. Thus, when adopting a prospective BIM application with uncertain effectiveness, it is essential for decision makers to justify BIM adoption before iterating the conventional practice of information processing with BIM.…”
Section: Introductionmentioning
confidence: 99%